Korelasi Jumlah Limfosit Dengan Anti Dengue IgG/IgM - Ai Kurniawati; Meri Meri; Amelia Amanda (Yayasan Literasi Sains Indonesia, 2022)
Dengue hemorrhagic fever (DHF) is a disease caused by infection with the dengue virus. DHF is an acute disease using clinical manifestations of bleeding that causes trauma and leads to death. DHF is caused by one of four virus serotypes according to the genus Flavivirus, family Flaviviridae. The diagnosis of DHF cases is supported by laboratory examination of IgG and IgM antibody parameters to determine whether they are positive or negative for DHF. Dengue IgG/IgM immunological examination is one of the crucial parameters in dengue assessment. Antibodies formed in dengue are neutralizing, anti-haemagglutinin, and anti-complement antibodies to classify primary and secondary DHF infections. Cells that play a role in the specific immune system are lymphocytes. B lymphocytes are part of adaptive immunity that can produce antibodies. Normally has an absolute lymphocyte count of 1.0-4.8 x 103/µL. The purpose of this study was to determine the relationship between lymphocyte count and anti-dengue IgG/IgM. The research method used in this research is Cross Sectional with Consecutive sampling technique. The results of the study based on the Spearman correlation statistic test obtained r = 0.082 and P = 0.667 for the relationship of Absolute Lymphocytes to IgG/IgM Results. The conclusion of this study is that there is a very weak and insignificant relationship between the number of lymphocytes and anti-Dengue IgG/IgM